Die Rolle der Mitogen-aktivierten Proteinkinasen beim Phänomen der ischämischen Präkonditionierung am Schweineherzen - Strohm, Claudia; Justus Liebig University Giessen (My University, 2002)
Der Hintergrund der Arbeit war die Beobachtung der ischämischen Präkonditionierung (Ischämietoleranz) am Schweineherzen. Unter ischämischer Präkonditionierung (IP) versteht man das Phänomen der kardialen Konditionierung durch kurze vorgeschaltete Ischämie- und Reperfusionszyklen gegenüber einer nachfolgenden längeranhaltenden Ischämie. Dabei verschiebt sich die Beziehung zwischen entstehender Infarktgröße (Ordinate) und Verschlusszeit (Abszisse) nach rechts. Die Erklärung für dieses Verhalten wurde in der vorliegenden Arbeit in der differentiellen Aktivierung der MAP-Kinasen gesucht. Dabei wurden vor allem drei Transduktionswege entdeckt, welche bei Ischämie und anschließender Reperfusion der linken absteigenden Koronararterie in dem minderdurchbluteten Myokardgewebe aktiviert werden. Es handelt sich um die extrazellulär-Signal-regulierten Proteinkinasen (ERKs), die Stress aktivierten-c Jun-NH2-terminalen Proteinkinasen (SAPKs / JNKs) und die p38-MAPKs, die ebenfalls zur Familie der Stress-aktivierten Proteinkinasen gehören. Die Aktivitätssteigerung der ERKs und SAPKs/JNKs durch kurze Ischämie- bzw. Reperfusionsphasen bewirkte einen Schutz des Myokards vor Infarktentstehung ('survival pathway'). Der sogenannte 'death-pathway' wurde über die p38-MAPKs aktiviert, d.h. sie erlangten ebenfalls Aktivitätssteigerung und bereits -maximum während einer Ischämieperiode, weitere wiederholende ischämische Zustände verringerten jedoch ihre Aktivität und ein folgender Reperfusionszyklus erzielte bereits Aktivitätsverlust bis zum Basiswert. Ihr Aktivitätsanstieg bedeutete im Gegensatz zu dem von ERKs und SAPKs/JNKs signifikant höhere Infarktgrößen. Die Auswirkungen der Blockade der Phosphorylierungskaskaden der MAPKs und deren Determinaten auf die Infarktgröße wurde mit Hilfe von spezifisch MAPKs-inhibierenden Substanzen untersucht. Bestätigung der 'in-vivo' erlangten Ergebnisse der Infarktentstehung erhielten wir durch proteinbiochemische Untersuchungen von Myokardbioptaten. Hierbei wurde Gewebe zu verschiedenen Zeitpunkten der Ischämie und Reperfusion, mit und ohne Substanzapplikationen in Phosphorylierungs- und Aktivitätsbestimmungen untersucht. Der Signalweg der ERKs wurde durch die experimentellen Substanzen PD98059 und UO126 spezifisch an zwei Stellen inhibiert. Eine lokale intramyokardiale Verabreichung der PD- und UO Substanzen mittels einer Mikropumpe direkt in das zu erwartende ischämische Herzgewebe zeigte, dass die Inhibierung eines Phosphorylierungsschrittes dieser Proteinkinasen eine Aufhebung der kardioprotektiven Wirkung eines vorgeschalteten IP-Zyklus bewirkte. Das heißt, in dem Diffusionsbereich der Substanzen entstanden keilförmige Infarkte, die von nicht-nekrotischem, geschütztem Gewebe umgeben waren. Kontrollversuche ohne Substanzapplikation oder die alleinige Infusion des Lösungsmittels der Substanzen verursachten keine Infarzierung des Herzmuskels. Ebenfalls ermöglichte uns dieses Infusionsverfahren die Verabreichung verschiedener Substanzkonzentrationen und die Erstellung von Dosis-Wirkungsprinzipien, die sich für die genannten Substanzen bei semilogarithmischem Maßstab in linearem Verlauf zeigten. Wurde die Phosphorylierungskaskade der p38-MAPKs mit SB203580, einem Imidazolderivat, inhibiert, entstand ein signifikant verzögerter Infarkteintritt, ohne das Auswirkungen auf das Zustandekommen der IP zu beobachten waren. Die systemische und intramyokardiale Infusion von Taxol zeigte eine signifikant erhöhte Infarktgröße und eine vollständige Aufhebung der Kardioprotektion der IP. Dies wurde durch die Inhibition des SAPKs/JNKs-Signalweges verursacht. Beide Applikationsarten des Transkriptionsgiftes Actinomycin-D erzielten eine Aufhebung des Schutzmechanismus von IP mit signifikant gesteigerten Infarktgrößen. Hierbei wurde die Phosphorylierungsintensität aller drei zytosolischen MAPKs inhibiert, jedoch konnte zusätzlich eine starke Verminderung des Phosphorylierungsstatus sowie des m-RNA-Levels der MAPKs-spezifischen Transkriptionsfaktoren c-Jun, Elk-1, c-Myc und ATF-2 festgestellt werden.

Stressful stimuli applied as brief pulse trains, condition most tissues in such a way, that they become more tolerant against longer lasting stresses, significantly delaying the onset of irreversible damage. This endogenous phenomenon, known as ischemic preconditioning (IP), renders the affected myocardium more resistant to a subsequent prolonged coronary occlusion by short transient periods of ischemia. The molecular mechanism of this increase in stress tolerance, especially that towards ischemia, is not entirely clear, but mitogen activated Proteinkinases (MAPKs), that are involved in the signal transduction pathways, may play a role. The MAPKs represent a superfamily of Pro-directed Ser/Thr Proteinkinases, that are involved in signal transduction from the plasma membrane to nuclear and cytoplasmic targets. Since the proto-oncogene based transcription factors are activated by membrane and cytoplasmic signalling cascades we studied the involvement of the three MAPKs pathways. The extracellular signal-regulated kinases: ERKs, the stress-activated/c-Jun N-terminal kinases: SAPKs/JNKs and p38-MAPKs. We found, that they react to brief ischemia and reperfusion in a very specific way. The ERKs activity moderately increased during brief ischemia but markedly during reperfusion, the SAPK/JNKs become active only during reperfusion and the weiß MAPKs were activated only during ischemia and deactivated during the following reperfusion and subsequent period of ischemia. Specific and selective activators and inhibitors have been used to differentiate between the three main MAP kinase pathways and to understand their role in IP. Our previous studies suggested a protective role of the ERKs and the SAPKs/JNKs cascade in the cardioprotective mechanism of IP. To further test this hypothesis, we studied the influence of the novel specific inhibitors of ERKs, PD98059 and UO126, the SAPKs/JNKs inhibitor Taxol and the transcription inhibitor Actinomycin-D (Act-D) in IP. The substances were infused intramyocardially and with the exception of PD also systemically. The influence of the inhibitors on infarct size was measured after a period of index ischemia and reperfusion with or without infusion of these agents prior and during IP. Biopsies of the areas of drug infusion were taken after IP. By Western blot analysis the phosphorylation of MAPKs and of their down-stream transcription factors were measured and the activities of the MAPKs were tested by 'in gel'-phosphorylation assays. Only small infarcts were detected in the control group animals with the IP period. Significant wedge-shaped infarcts were seen around the area of the microinfused tool drugs. The effects of the substances were concentration dependent. At the end of IP we observed in the PD and UO treated animals a significant decrease in phosphorylation and activities of ERKs. In Taxol treated animals the phosphorylation of SAPKs/JNKs was inhibited and in the Act-D treated animals the phosphorylation state of all three cytosolic MAPKs was decreased. We demonstrated for the first time in vivo that the inhibition of ERKs and SAPKs/JNKs resulted in a complete cancellation of IP. On the other hand, our results with the specific inhibitor of the p38-MAPK pathway, SB203580, have suggested a negative role of p38-MAPKs during ischemia in the same in vivo model. When SB203580 was infused systemically infarct size was significantly reduced. Ischemia with and without SB203580 significantly increased phospho-p38-MAPKs with a maximum reached at 20 min but activity was less at 30 and 45 min under the influence of the inhibitor. Measurements of p38-MAPK activities in situations where SB203580 was present during in-gel phosphorylation showed significant inhibition of p38-MAPK activities. We investigated also the effect of local and systemic infusion of SB203580 on the cardioprotection induced by IP. The infusions of SB203580 before and during IP protocol did not influence the infarct size reduction mediated by IP. The observed protection of the myocardium against ischemic damage by SB203580 points to the negative role of the p38-MAPKs pathway during ischemia. We hypothesised, that SB203580 can protect the heart against the consequences of prolonged ischemia. A common feature of all MAPKs is their ability to phosphorylate the transactivation domain of numerous transcription factors and thereby modulate their transcriptional activities. The transcription factors Elk 1, ATF-2, c-Myc and c-Jun are substrates for the three distinct classes of MAPKs. To test the hypothesis that a nuclear mechanism is involved in IP we studied the influence of the inhibitors on the phosphorylation state of these transcription factors. The application of all tested tool drugs significantly inhibited the ischemia-induced phosphorylation of the nuclear transcription factors and in the case of Actinomycin-D also the m-RNA level of these transcription factors was decreased. However, it cannot be excluded that MAPKs activations during IP and ischemia/reperfusion do have beside a nuclear mechanism, also important effects outside the nucleus.
The role of mitogen-activated protein kinases in the phenomenon of ischemic preconditioning in pig hearts
Keywords: ddc:630